(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article provides a rationale for the parameters of the front plow angle gauge, which ensures high-quality implementation of the technological process according to agrotechnical requirements with the least energy consumption, as well as a design diagram of the front plow with angle gauges and a diagram for determining the longitudinal distance between the body and the angle gauge. Theoretical and experimental studies have established that the longitudinal distance between the body plowshare and the angle cutter is at least 27 cm and between the disc blade and the angle cutter 16 cm ensures the required quality of tillage of the front plow in accordance with established agrotechnical requirements.